Fiber quality and methane production in legume silage with carbohydrate sources - López-Herrera, Michael (2021)
The objective of this research was to determine the effect of the carbohydrate source and the legume species on fiber quality, gas production and methane concentration in silage. The experiment was carried out between August 2015 and February 2016. A 4x4 factorial design was used, with four legumes (Vigna unguiculata, Arachis pintoi, Cratylia argentea, Erythrina poeppigiana) and 4 sources of carbohydrates (sugar cane molasses, dried citrus pulp, ground corn and Square banana [GC]). Microsilos were used, which were stored for 50 days and indicators of interest were measured at the opening. The information analysis was made using linear and mixed models. It was determined that, the mixtures ensiled with shrub legumes generated higher fiber content, although of lower quality, due to a higher content of lignin compared to the silage of herbaceous legumes. On the other hand, the CG was the source of carbohydrates that altered the quantity and quality of the fiber in the silage, due to the higher content of NDF and lignin of the fruit. These variations in the quality and quantity of the fiber influenced PGas production (ml/gDM) while, methane production (L/kgDM) in the gas was affected by the quality of the fiber and the content of condensed tannins in the forage. In conclusion, the species and the source of carbohydrates generate differences in the quantity and quality of the fiber, which affects the gas production and methane concentration of the legume silage. This is how the silage of Arachis or Erythrina combined with ground corn was the one with the lowest production and concentration of methane.